Lexicon of Uma Baloko Establishment of Kodi Speech Community of Southwest Sumba - Paulina Maria Yovita Kosat; Mirsa Umiyati (RETORIKA: Jurnal Ilmu Bahasa, 2018)
Abstract—Studies on interrelation and interplaying between ecology and language of human have long been of heated debate. Mostly they remain in how linguistic forms are indirectly used within the environment to record all kinds of activities. This study examines the lexicons and their sense relation used in the construction of Uma Bokolo of Kodi speech community, Southwest Sumba, from the perspective of ecolinguistic theory. Data were collected by observing the house and deep-structurally interviewing two senior inhabitants of Kodi. Data analysis was done by tringulation method. The results show that there are 55 lexicons consisting of 41 lexicons of noun-formed and 14 lexicon verb-formed. Each of these lexicons is divided into two categories, namely the category of biotic and abiotic environments. In addition, from the results of the data analysis, it is also found that there are 23 noun lexicon of base form and 17 of compound word form. Each of the lexicon comprises 12 lexicons with N-N pattern, 2 lexicons with N-V pattern, and 3 lexicons patterned N-A. There are three kinds of sense relation found, such as hyponymy, synonymy and hypernymy. Keywords: Ecolinguistic; Lexicon; Sense Relation; Uma Baloko